Berbamine inhibits RANKL- and M-CSF-mediated osteoclastogenesis and alleviates ovariectomy-induced bone loss - Qi, Guobin; Jiang, Zengxin; Lu, Wei; Li, Defang; Chen, Weibing; Yang, Xiuying; Ding, Lei; Yuan, Hengfeng (Frontiers in Pharmacology, 2022)
Osteoporosis is a common public health problem characterized by decreased bone mass, increased bone brittleness and damage to the bone microstructure. Excessive bone resorption by osteoclasts is the main target of the currently used drugs or treatment for osteoporosis. Effective antiresorptive drugs without side effects following long-term administration have become a major focus of anti‐osteoporotic drugs. In the present study, we investigated the effect of berbamine, a small molecule natural product from Berberis amurensis Rupr, a traditional Chinese medicine, on RANKL-induced osteoclast differentiation in vitro and ovariectomy-induced bone loss in vivo. The results demonstrated that berbamine at a safe and effective dose inhibited osteoclastogenesis and bone resorption function in vitro by suppressing the nuclear factor-κB signaling pathway. In addition, berbamine protected against osteoporosis by inhibiting osteoclastogenesis and bone resorption function without affecting osteogenesis in the ovariectomy mouse model. These findings revealed that berbamine has a protective role against osteoporosis and may represent a novel promising treatment strategy for osteoporosis.